Preparation, Characterisation, and Photocatalytic Behaviour of Co-TiO2 with Visible Light Response. (17th January 2008) - Amadelli, Rossano; Samiolo, Luca; Maldotti, Andrea; Molinari, Alessandra; Valigi, Mario; Gazzoli, Delia
Abstract : The preparation of cobalt-modified TiO 2 (Co-TiO 2 ) was carried out by the incipient impregnation method starting from commercial TiO 2 (Degussa, P-25) and cobalt acetate. XPS data show that cobalt is incorporated as divalent ion, and it is likely present within few subsurface layers. No appreciable change in structural-morphologic properties, such as surface area and anatase/rutile phase ratio, was observed. Conversely, Co addition brings about conspicuous changes in the point of zero charge and in surface polarity. Diffuse reflectance spectra feature a red shift in light absorption that is dependent on the amount of cobalt. The influence of cobalt addition on the performance of TiO 2 as a photocatalyst in the degradation of 4-chlorophenol and Bisphenol A is investigated. The results show that the modified oxide presents a higher photoactivity both for illumination with UV-visible (λ > 360  nm) and visible light (λ > 420  nm; λ > 450  nm), and that this enhancement depends on the amount of the added species and on the final thermal treatment in the preparation step. We also show that Co-TiO 2 is a more active catalyst than pure TiO 2 for the reduction of O 2 in the dark, which is an important reaction in the overall photocatalytic processes.